Sleep and thermoregulation. Issue 15 (June 2020) - Harding, Edward C; Franks, Nicholas P; Wisden, William
Abstract : In homeothermic animals sleep preparatory behaviours often promote thermal efficiency, including warmth-seeking, adopting particular postures (curling up, head tucking) and nest building, all promoting warmer skin microclimates. Skin warmth induces NREM sleep and body cooling via circuitry that connects skin sensation to the preoptic hypothalamus. Coupling sleep induction and lower body temperature could serve to minimise energy expenditure or allow energy reallocation. Cooling during NREM sleep may also induce transcriptional changes in genes whose products facilitate housekeeping functions or measure the time spent sleeping.